Kinerja Keterlanjutan dan Nilai Perusahaan: Sebuah Kajian Teoritis - Arin Pranesti; Kharisma Saski Larasati; Arsy Widiyanti (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The Government of Indonesia through The Financial Services Authority (Orotitas Jasa Keuangan-OJK) has encouraged public companies to report performance related to Environmental, Social, and Governance (ESG) activities as part of supporting the achievement of sustainable finance in Indonesia. This study aims to determine whether there is a long-term impact on sustainability performance which is represented in firm value. This research is a literature review research sourced from scientific journal articles that are adapted to the research topic. The results of the study indicate that the impact of sustainability performance needs to be investigated further because the results of previous studies showed inconclusive results. Even so, ESG performance should be a good signal because the company has considered other aspects besides short-term profits. ESG performance reporting policies required by OJK need to be balanced with a strong legal environment and proper supervision. This will improve the quality of information received by users of financial statements that can be reflected in the value of the company.